Metagenomic Binning Recovers a Transcriptionally Active Gammaproteobacterium Linking Methanotrophy to Partial Denitrification in an Anoxic Oxygen Minimum Zone - Cory C. Padilla; Anthony D. Bertagnolli; Laura A. Bristow; Neha Sarode; Jennifer B. Glass; Bo Thamdrup; Frank J. Stewart (Frontiers in Marine Science, 2017)

Biogeochemical and metagenomic analysis of nitrite accumulation in the G ulf of M exico hypoxic zone - Laura A. Bristow; Neha Sarode; John Cartee; Alejandro Caro‐Quintero; Bo Thamdrup; Frank J. Stewart (Limnology and Oceanography, 2015)
The Louisiana Shelf in the Gulf of Mexico experiences recurrent bottom water hypoxia under summertime eutrophic conditions. The onset, maintenance, and breakdown of hypoxia are associated with dynamic microbial biogeochemical cycles. However, the distribution of microbial taxa and metabolisms across Shelf oxygen gradients remains under‐characterized. We combined biogeochemical analyses of nitrogen (N) distributions and metabolic rates with metagenomic and metatranscriptomic analysis of summertime Shelf waters. Samples from an east–west transect during July 2012 revealed an inverse relationship between nitrite and oxygen concentrations, with concentrations exceeding 1 μmol L −1 at ∼ 50% oxygen saturation and reaching 4.6 μmol L −1 at the most oxygen‐depleted sites. Historical data confirms that nitrite accumulation occurs frequently in this region both above and below the hypoxic threshold. Experimental incubations demonstrated a strong decoupling between the two steps of nitrification, with ammonia oxidation proceeding up to 30 times faster than nitrite oxidation under low oxygen. 16S rRNA gene, metagenome, and metatranscriptome sequencing revealed a diverse microbial community, stratified over shallow (